Older patients' experience of living with cognitive impairment related to hormone therapy for breast cancer: A qualitative study. (April 2022) - Tenda, Yasuko; Miyashita, Mika; Yamada, Akimitsu; Shimizu, Chikako; Nakayama, Kanako; Honma, Naoko; Taira, Naruto; Sawaki, Masataka
Abstract: Purpose: Patients with breast cancer may develop cognitive impairment as a result of hormone therapy and aging. This study aimed to describe older patients' experience of cognitive impairment related to hormone therapy for breast cancer. Methods: A qualitative and descriptive design was used. Semi-structured interviews were conducted with 11 patients asking about their experience in daily life related to their cognitive impairment. Study participants were evaluated by cancer-specific geriatric assessment. Inductive content analysis was conducted using the interview records. Results: Three themes emerged from the patients' narrative data: recognizing of cognitive impairments, impacts on mental health, and coping with cognitive impairments. Recognizing of cognitive function consisted of two categories: perception of cognitive changes and acknowledging their cognitive function status through interacting with others. Impacts on mental health consisted of six categories: decreased motivation for social activities, upset by perception of cognitive decline, concerns about impacts of cognitive impairment on treatment of breast cancer, concerns about the care burden of their family, concerns about progression of cognitive impairments, and feeling secure that their cognitive impairment is not unusual. Coping with cognitive impairments consisted of two categories: coping with problems related to cognitive impairment and trying to maintain and improve cognitive function. Conclusion: Oncology nurses should assess cognitive function and complete a comprehensive evaluation of older patients receiving hormone therapy for breast cancer. An evaluation of cognitive function would enable a tailored approach to education and support to enhance coping ability in the longer term. Highlights: Older women receiving adjuvant hormone therapy for breast cancer reported cognitive impairment. Coping strategies were used to solving problems and enhance cognitive function. Comprehensive geriatric assessment is useful for understanding the true nature of older patients' health issues.